The Effect of Inflammation on the Healing Process of Acute Skin Wounds Under the Treatment of Wounds with Injections in Rats - Stupin V; Manturova N; Silina E; Litvitskiy P; Vasin V; Artyushkova E; Ivanov A; Gladchenko M; Aliev S (Dove Medical Press, 2020)
Victor Stupin,1 Natalia Manturova,2 Ekaterina Silina,3 Petr Litvitskiy,4 Vitaly Vasin,1 Elena Artyushkova,5 Alexander Ivanov,6 Mikhail Gladchenko,5 Salekh Aliev1 1Department of Hospital Surgery No 1, Pirogov Russian National Research Medical University, Moscow, Russia; 2Department of Plastic and Reconstructive Surgery, Cosmetology and Cell Technologies, Pirogov Russian National Research Medical University, Moscow, Russia; 3Department of Human Pathology, I.M. Sechenov First Moscow State Medical University (Sechenov University), Moscow, Russia; 4Department of Pathophysiology, I.M. Sechenov First Moscow State Medical University (Sechenov University), Moscow, Russia; 5Research Institute of Experimental Medicine, Kursk State Medical University, Kursk, Russia; 6Department of Histology, Embryology, and Cytology, Kursk State Medical University, Kursk, RussiaCorrespondence: Ekaterina Silina Department of Human PathologyI.M. Sechenov First Moscow State Medical University (Sechenov University), Trubetskaya Str, 8, Moscow 119991, RussiaEmail silinaekaterina@mail.ruPurpose: To study the effects of inflammation on the healing process of rats’ acute skin wounds during treatment with different injections.Methods: The study was carried out on Wistar rats, on which square wounds were simulated in the back region. Four groups of wounds were studied. On the day of the simulation (day 0), solutions of the drugs were injected into the wounds: an isotonic sodium chloride solution (Control group), mesenchymal stem cells (SC group), collagen (Collagen group), and a deproteinized hemoderivative of calf blood (DHB group). Within 2 weeks, the wound healing process was assessed by observing and calculating changes in the wound areas, temperatures, and epithelialization levels. On days 3, 7, and 14, wound tissue samples were taken for histological examination, morphological analysis of the healing process, and quantitative assessment of granulation layers’ leukocyte infiltration.Results: A correlation between the process of inflammation and epithelization during the healing of skin wounds was established. The anti-inflammatory effect of SC injection on the wound edge tissues was determined, as well as the pro-inflammatory effect of DHB, and the absence of effects on the inflammation course under the collagen treatment. Compared to the control group, the transition from the exudative phase of inflammation to the proliferative phase was faster, as well was wound epithelialization in the SC and Collagen groups. A negative correlation between the level of tissue temperature in the center of wounds and their area were recorded, which intensified over time.Conclusion: The severity and duration of the inflammation process during wound healing were ambiguous with the use of different injection treatments. This should compel clinicians to use different markers of drug therapy effectiveness during wound healing. Excessive leukocyte infiltration with a low temperature of wounds and a large scab were markers of delayed wound healing.Keywords: skin wound, inflammation, leukocytes, epithelialization, collagen, stem cells, deproteinized hemoderivative of calf blood